POSITIVE POLITENESS STRATEGIES IN BUSINESS CORRESPONDENCE BETWEEN DETRACK SYSTEMS AND ITS CLIENTELE - Aini, Hilya; Simatupang, Ervina CM (English Review: Journal of English Education, 2024)
Positive politeness is crucial in business communication as it fosters respectful rapport, enhances trust through assurances, and mitigates conflicts, thereby promoting effective interactions and fostering successful relationships. This study investigates the specific politeness strategies employed in business correspondence between Detrack Systems and its clientele and their roles in facilitating effective communication. The method used is qualitative analysis. Results reveal that several types of positive politeness strategies were used; specifically, strategy 1 was employed in ten cases, strategy 2 in five cases, strategy 3 in one case, strategy 5 in three cases, strategy 6 in six cases, strategy 9 in two cases, strategy 10 in five cases, strategy 11 in three cases, strategy 13 in three cases, strategy 14 in four cases, and strategy 15 in seven cases. In total, these strategies were observed 49 times across the analyzed emails. Through this analysis, it's clear that Detrack Systems and its clients consistently use these strategies. The roles of these positive politeness strategies in effective communication are to foster trust, facilitate collaboration, enhance customer satisfaction, promote transparency, assert reciprocity and help maintain positive relationships.